How well does Brazil's environmental law work in practice? Environmental impact assessment and the case of the Itapiranga Private Sustainable Logging Plan - Eve, Evaldice; Arguelles, Francisco A.; Fearnside, Philip Martin (Environmental Management, 2000)
The Itapiranga Sustainable Logging Plan provides an example of how Brazil's licensing system functions for logging companies in the state of Amazonas. Two questions need to be dealt with: 'How sustainable can logging in the Amazon be?' and 'What and how effective are existing legal mechanisms to deal with logging projects?' The environmental impact assessment (EIA) and environmental impact statement (EIS, known as the RIMA in Brazil), present relatively detailed accounts of biodiversity and the need to adopt conservation strategies to protect it. However, social and health impacts are only superficially addressed. The economic sustainability of the operation over multiple cycles is not demonstrated. The multidisciplinary teams responsible for the EIA and EIS (RIMA) reports are hired by the project proponent, an arrangement inherently carrying the risk of biasing the result. Logging reduces biodiversity, releases greenhouse gases and inflicts social and health costs. These impacts reduce the ability of Amazonian forests to provide environmental services and to supply food and livelihood security to local populations. The reports inflate positive effects such as employment: the estimated number of jobs was cut by more than half in a revision made after the EIA and EIS (RIMA) had been approved. Not only do the reports need to be more realistic in assessing both positive and negative consequences of proposed projects, but better means are needed to ensure that promised mitigatory measures are enforced in practice. Many of the lessons that can be drawn from the Itapiranga Plan are not unique to logging projects and apply to licensing of development activities generally in Brazil and elsewhere.The Itapiranga Sustainable Logging Plan provides an example of how Brazil's licensing system functions for logging companies in the state of Amazonas. Two questions need to be dealt with: `How sustainable can logging in the Amazon be?' and`What and how effective are existing legal mechanisms to deal with logging projects?' The environmental impact assessment (EIA) and environmental impact statement (EIS, known as the RIMA in Brazil), present relatively detailed accounts of biodiversity and the need to adopt conservation strategies to protect it. However, social and health impacts are only superficially addressed. The economic sustainability of the operation over multiple cycles is not demonstrated. The multidisciplinary teams responsible for the EIA and EIS (RIMA) reports are hired by the project proponent, an arrangement inherently carrying the risk of biasing the result. Logging reduces biodiversity, releases greenhouse gases and inflicts social and health costs. These impacts reduce the ability of Amazonian forests to provide environmental services and to supply food and livelihood security to local populations. The reports inflate positive effects such as employment: the estimated number of jobs was cut by more than half in a revision made after the EIA and EIS (RIMA) had been approved. Not only do the reports need to be more realistic in assessing both positive and negative consequences of proposed projects, but better means are needed to ensure that promised mitigatory measures are enforced in practice. Many of the lessons that can be drawn from the Itapiranga Plan are not unique to logging projects and apply to licensing of development activites generally in Brazil and elsewhere.The Itapiranga Sustainable Logging Plan is analyzed as an example of how the licensing system functions for logging companies in the Brazilian state of Amazonas. While environmental impact assessments and statements detail biodiversity and the need to implement conservation strategies, social and health impacts are superficially considered. The economic sustainability of the operation over multiple cycles is not proven, and reports prepared by multidisciplianry teams hired by the project proponent inflate positive effects, such as employment.
Keywords: Environmental Impact Assessment (eia); Decision Making; Economic And Social Effects; Environmental Engineering; Environmental Protection; Laws And Legislation; Logging (forestry); Strategic Planning; Sustainable Development; Environmental Impact; Economic Impact; Environmental Economics; Environmental Impact Assessment; Logging; Sustainability; Biodiversity; Economic Aspect; Environmental Impact Assessment; Environmental Protection; Government; Policy; Review